Coriolanus - Shakespeare, William 1564-1616. (London : Macmillan, 1950)
The Catholic University of America Speech and Drama Department presents "Coriolanus," by William Shakespeare, directed by James D. Waring, performances coached by Josephine McGarry Callan, setting and lighting by James D. Waring, costumes by Joseph Lewis.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Shakespeare, William; Theater programs -- Washington (D.C.); Theater programs -- 1961.